Evaluating vendor managed inventory systems: how incentives can benefit supply chain partners - Birim, Sule; Sofyalioglu, Cigdem (Journal of Business Economics and Management, 2017)
In a vendor managed inventory (VMI) system, the effects of financial incentives on the entire supply chain (SC) and on the individual firms are investigated in this study. To this end, order management, order replenishment and inventory control activities of a two-echelon SC are examined via modeling using discrete event simulation. By determining the appropriate parameters for the incentives with scenario analysis, balanced profit distribution between buyers and a supplier in VMI is established. Simulation outputs of the traditional model, VMI only and VMI with incentives models are compared based on profits with paired comparisons. In VMI with incentives, both buyers, and the supplier experience higher benefits than the traditional system. This study provides a new method which eliminates the unbalanced benefit distribution due to VMI and offers almost equal benefits to the participating firms. With financial incentives, firms are encouraged to share information with each other to work in a coordinated SC.